Determinant Of Sharia Stock Returns And The Impact Of The Pandemic As Moderation Variables (Case Study of Jakarta Islamic Index (JII) for the 2017-2021 Period) - Muhammad Ridha Irsyadillah; Atika Rukminastiti Masrifah (Jurnal Akuntansi Indonesia, 2023)
ABSTRACT